Effects of Hormone Replacement Therapy (HRT) on the body weight, blood pressure and vaginal bleeding in menopausal women (Faculty of Medicine Universitas Indonesia, 2002)
This study was a descriptive, retrospective trial conducted in 29 menopausal women. Each patient received treatment with conjugated equine estrogen (CEE) 0.625 mg/day + medroxyprogesterone acetate (MPA) 5 mg/hari continuously for the period of 6 months. The average age of menopause was 53.7 years with duration of menopause of 5.5 years. The education level of patients was Senior High School and higher. During the period of 6 months of continuous combined HRT, a significant increase of body weight and systolic blood pressure was found, while diastolic blood pressure did not have any significant change. Vaginal bleeding in the form of spotting occurred in 69% of the patients during the use of continuous combined HRT. (Med J Indones 2002; 11:11-4)Keywords: continuous HRT, menopause, body weight, blood pressure, bleeding